Can Gerhard Schröder Do It? : Prospects for Fundamental Reform of the German Economy and a Return to High Employment - Irwin L. Collier (Institute for the Study of Labor (IZA), 2004)
The year 2003 has witnessed several major reform policy initiatives in Germany intended to contribute to a solution to Germany's high unemployment problem and to improve the longrun sustainability of its social welfare policies. These economic reforms are discussed within a larger macroeconomic context.
Keywords: E65; J68; O52; 330; labor market reform; social policy reform; unemployment; Wirtschaftsreform; Sozialreform; Arbeitsmarktflexibilisierung; Makroökonomischer Einfluss; Beschäftigungseffekt; Deutschland